Differences in the Nutritional Status of the Elderly with Hypertension in Rural and Urban Areas - Ni Kadek Novi Ansari; Ni Luh Putu Eva Yanti; Desak Made Widyanthari; Putu Ayu Sani Utami (Talenta Publisher, 2024)
Individuals with excess weight are more likely to experience increased blood pressure compared to those with normal weight. Hypertension is particularly prevalent among the elderly population. Additionally, the living environment whether urban or rural can influence the nutritional status of elderly individuals with hypertension. This study aims to compare the nutritional status of elderly individuals with hypertension residing in rural and urban areas. A quantitative comparative cross-sectional design was employed, and purposive sampling was used to select 152 participants. Data collection included measurements of body weight using digital scales, height or knee height using a stadiometer, and blood pressure using a digital sphygmomanometer. The results, analyzed using an independent t-test, revealed a significant difference in the nutritional status of elderly individuals with hypertension between rural and urban areas (p-value = 0,007), with a mean difference of 1,476. The findings indicate that the nutritional status of elderly individuals in rural areas is better compared to their urban counterparts. This difference is influenced by food intake and physical activity levels. Elderly individuals with hypertension in rural areas tend to consume homegrown foods and agricultural products, contributing to their healthier status. They should continue engaging in physical activities like gardening or farming. In contrast, elderly individuals in urban areas face challenges due to the availability of ready-to-eat or processed foods. It is essential for them to adopt healthier dietary habits and increase physical activity through walking or participating in community-based health programs to improve their nutritional and overall health status.